Risk Factors for Surgical Treatment in Gastric and Colorectal Cancer Patients with Low Socioeconomic Status - Kulah, B.; Ergul, Z.; Akinci, M.; Kulacoglu, H. (Scientific Journal of Medical Science, 2014)
Surgery is the only potentially curative treatment option for gastric and colorectal cancer patients. Stage at diagnosis is the most important prognostic factor and closely related with socioeconomic status. Authors aimed to compare the risk factors influencing presentation and outcomes of surgical treatment of gastric and colorectal cancer patients with low socioeconomic status. Clinicopathologic characteristics of 112 consecutive patients in low socioeconomic area and outcomes of their surgical treatments were compared to identify the risk factors for each type of cancer. Clinicopathologic characteristics were similar in both groups. Elderly patients had comprised 30% of all patients. Advanced stage diseases were noted in 82% of gastric cancer patients and 78.6% of colorectal cancer patients. Curative resection rates were 19.6% for gastric cancers and 51.8% for colorectal cancers. Emergency surgical procedures were performed in 35% of patients with colorectal cancer. Postoperative morbidity rates were 18% and 23%, mortality rates were 5.4% and 10.7% in gastric and colorectal cancer patients, respectively.Advanced age and advanced stage at diagnosis significantly influence the results of surgical treatment of gastric and colorectal cancer patients. Morbidity and mortality rates are also significant correlated with high ASA scores, emergency procedures and curative resections in colorectal cancer patients. Optimal balance should be established between the goals of surgical treatment and acceptable risks of surgery for a good quality of life. Improvement of socioeconomic status may make considerable contribution to surgical treatment.